Employee engagement in workspaces of physical office environment (POE) - Abdul Hamed, Sapiah; Mohd. Hussain, Mohd. Ramzi; Md Jani, Haza Hanurhaza; Sabri, Syikh Sazlin Shah; Rusli, Nazrul (Otago Polytechnic, New Zealand, 2025)
This paper explores the intricate relationship between employee engagement and workspaces in the physical office environment (POE). Workspaces refer to designated areas or environments, either physical or digital, where individuals or teams perform their tasks and activities. Traditionally, workspaces are physical offices or workstations equipped with the necessary tools and resources. They are characterized by individual enclosed spaces that influence employee mood, motivation, and employee engagement at the workplace. The aim of this paper is to examine how the physical office environment contributes to employee engagement. This study employs analytical reviews of related articles selected from Google Scholar to justify the influence of the physical office environment on employee engagement in workspaces. A content analysis is used to examine the literature framework, applying a taxonomical table method to systematically categorize, organize, and interpret the findings. The results reveal the significance of the physical office environment for employees. When supported by a positive and well-equipped workspace, employees are more likely to experience satisfaction and demonstrate a commitment to the organization. Creating a physical office environment that reflects an organization's values and meets the diverse needs of its employees is essential to fostering a vibrant and productive workplace. In conclusion, the study confirms that the physical office environment is a strategic asset that significantly shapes employee attitudes instilling a sense of belonging and motivation. When employees feel supported by their surroundings, they are more likely to be engaged, committed, and aligned with the organization's goals. The physical office environment is not merely a backdrop but a strategic factor that can influence the engagement and success of an organization.